Mechanistic insight into CdSe nanoplatelet-sensitized upconversion: size and stacking induced effects. Issue 3 (13th December 2022) - VanOrman, Zachary A.; Weiss, Rachel; Bieber, Alexander S.; Chen, Banghao; Nienhaus, Lea
Abstract : A unique triplet–triplet annihilation-based upconversion mechanism was observed upon studying the effect of the lateral size of CdSe nanoplatelets, with an interplay of the power threshold and upconversion efficiency. Abstract : CdSe nanoplatelets (NPLs) have been reported as triplet sensitizers for photon upconversion (UC). However, their UC quantum yields lag behind more conventional systems. Here, we take advantage of their one-dimensional quantum confinement to decouple effects caused by the energetic driving force and lateral size. A surprising anti-correlation between the power threshold I th and the UC quantum yield based on the NPL size is found. We attribute this result to two distinct triplet–triplet annihilation mechanisms based on the NPL lateral dimension and degree of NPL stacking—mediated either by molecular diffusion or triplet energy diffusion.